A Horseshoe-shaped Dermoid - Suwarna Suman (Case Reports in Clinical Practice, 2024)
Dermoid cysts are congenital choristomas. Orbital dermoids are usually encapsulated cystic lesions and are oval, round, or hourglass in shape. Here, we present an unusual case of an external angular dermoid with a unique horseshoe-shaped appearance in a 19-year-old male.